Etika bisnis sebagai acuan meningkatkan kepuasan konsumen : (studi pada bisnis online) - salsabilla, putri yulia (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has drastically changed the business landscape. Online shopping is now the top choice for many consumers due to the convenience and variety of products offered. online business has become an inseparable part of our lives. Platforms such as Lazada, Shopee, Tokopedia, and Bukalapak offer convenience for consumers to access various products with a variety of payment options, ranging from bank transfers to on-site payments. However, behind this convenience, there are challenges for businesses to maintain integrity and consumer trust. Business ethics has become increasingly important to ensure that online transactions run smoothly and fairly. By applying the principles of business ethics, sellers can build a good reputation, increase customer loyalty, and ultimately achieve sustainable business success.